(untitled) (Research, Society and Development, 2022)
This study assessed the influence of traditional (TradAC) and conservative access (ConsAC) with different restorative techniques on the percentage of hard tissue removed (%HTR) and on the fracture resistance of mandibular premolars. 45 premolars were scanned in a micro-computed tomography and assigned into four groups according to access (TradAC or ConsAC) and restorative technique: composite resin (CR) or fiber post (FP) + CR. After post preparation, the teeth were rescanned to determine the volume enlargement and %HTR from the crown and root canal. After restoration, the load at fracture was recorded. Data were analyzed statistically by one-way ANOVA and Tukey’s post-hoc test, ANOVA repeated measure, and chi-square tests (P<0.05). TradAC (RC or FP) resulted in the increase (Δ%) of root canal volume and hard tissue removed up to 14 mm (%) in comparison with ConsAC (RC or FP). TradAC + FP removed a greater percentage of hard tissue from the crown when compared to TradAC + CR. The percentage of hard tissue removed in the crown in the ConsAC groups was statistically lower than in the TradAC groups. The control group showed higher fracture resistance than all experimental groups, with no differences among the latter. Restorable fracture patterns were more prevalent. Traditional endodontic access cavities removed a higher percentage of dentine than conservative endodontic access cavities. However, no differences in fracture resistance were observed. Restorations using composite resin or fiber post associated with composite resin showed similar results of fracture resistance.